1977
DOI: 10.1002/app.1977.070210205
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and mechanical properties of injection‐molded specimens of two‐phase polymer blends

Abstract: SynopsisAn experimental study was carried out to investigate the moldability of polymer blends which form two phases in the molten state and the effect of mixing on the morphology and mechanical porperties of molded specimens. Blends of polystyrene with polypropylene and blends of polystyrene with high-density polyethylene were used for this study. A plunger-type injection molding machine (Van Dorn) was employed for molding specimens. To improve the mixing performance of the plunger machine, a Static Mixer (Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Blends of polypropylene (PP) for improving properties suited to some specific application were extensively studied with a large number of polymers, including polyethylene, [1][2][3][4][5] polycarbonate, 6 polyamide, [7][8][9][10] polystyrene, 11,12 acrylonitrile-butadienestyrene (ABS), 13 ethylene-vinyl acetate (EVA), 14 elastomers. [15][16][17][18] However, the blends of PP and PP grafted with maleic anhydride (PP-g-MA) seem to have been scantily studied.…”
Section: Introductionmentioning
confidence: 99%
“…Blends of polypropylene (PP) for improving properties suited to some specific application were extensively studied with a large number of polymers, including polyethylene, [1][2][3][4][5] polycarbonate, 6 polyamide, [7][8][9][10] polystyrene, 11,12 acrylonitrile-butadienestyrene (ABS), 13 ethylene-vinyl acetate (EVA), 14 elastomers. [15][16][17][18] However, the blends of PP and PP grafted with maleic anhydride (PP-g-MA) seem to have been scantily studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been found [1][2][3][4][5][6][7][8][9][10][11][12] that both components in the blends (with one crystallizable component) may influence each other giving rise to very interesting effects such as: depression of the melting temperature of the crystallizable component, decrease or increase of its crystallinity degree and of the crystallization rate, change in morphological structure and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently the morphology and physical properties of isotactic polypropylene -atactic polystyrene blends were investigated [6,12,23,24]. It was found that a melting peak area is linearly proportional to the blend composition indicating [12] a high degree of dispersion in the blends prepared by injection molding using a screw static mixer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of processing conditions on the state of dispersion of the rubber phase plays an important role in the morphology of the blend formed, and hence on its resulting properties [7][8][9][10]. Three distinct types of morphologies that are evident from its fractured surface are separated, core and shell, and mixed type.…”
mentioning
confidence: 99%